Psychological Well-Being (PWB) dan Pengambilan Keputusan untuk Mengikuti Konseling Genetika pada Orangtua Anak dengan Talasemia Mayor - Costrie G. Widayanti; Kartika Sari Dewi (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
Parents' understanding about psychological well-being could affect their efforts in facing and accepting the children with thalassemia major. Genetic counseling and genetic screening are some attempts made to provide an understanding about this illness. There are some factors that affect parents' decision to enroll a genetic counseling or even a genetic screening.The aim of this research is to find out parents' psychological well-being and their decision to enroll a genetic counseling. Subjects in this research are parents of the children with thalassemia major that live in Central Java. Subjects are about 25-45 years old. The hypothesis of this research is “there is a positive correlation between psychological well-being and the decision to enroll a genetic counseling”. Data analysis show r = 0.624; p> .05 which mean that there is no significant correlation between psychological well-being and the decision to enroll a genetic counseling.Keywords: psychological well-being, genetic counseling, thalassemia major